EDUKASI TENTANG PEMAKAIAN DISPOSIBLE DIAPERS DENGAN KEJADIAN RUAM POPOK PADA IBU YANG MEMILIKI BAYI USIA 0-12 BULAN - Kristin Natalia; Susilawati Susilawati; Aswani Aswani; Egi Nabila; Aldian Waruwu (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
One of the causes of diaper rush (diaper rash) is when the mother does not immediately change the baby's full diaper. This causes redness of the baby's skin, moist and when rubbed it can cause skin irritation. The purpose of this education is to guide and teach mothers who have babies to know how to use diapers properly and correctly so that babies do not get diaper rash. This education is analytic in nature with a cross sectional research design with a sample of 15 infants taken using a porposive sampling technique. Data analysis used bivariate analysis with chi-square test statistical test. The results can be seen that from 15 respondents, most of the babies who wore disposable diapers were 9 people (60.0%) who had diaper rash as many as 8 people (53.3%) and 1 person (6.7%) who did not have diaper rash. ) while 6 people (40.0%) did not wear disposable diapers, and 6 people did not have diaper rash (40.0%). Based on the results of the Chi-square test statistical analysis obtained p value <0.05, which means that there is a significant relationship between the use of disposable diapers and the incidence of diaper It is hoped that mothers who have babies can pay more attention to the condition of the baby's diaper, if it is full, it should be replaced with a new diaper and clean the baby's skin after urinating or defecating.